Games in Teaching Speaking of Indonesian Language for Non Native Speakers (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
Indonesian language for non-native speakers is considered difficult because its position as a second language. Therefore, BIPA speaking students ask for certain models and techniques in learning so that BIPA students can master Indonesian properly according to their level. This research is a qualitative descriptive study conducted with the aim to study and describe the application of techniques in learning to speak BIPA Beginner Level (A-1) at IAIN Surakarta. This research was conducted at IAIN Surakarta with 6 successful BIPA learners (A-1). Data collection techniques used were observation, interview, and documentation techniques. The data analysis technique used is interactive analysis, namely data reduction, data presentation, and conclusion conclusions. The results of this study are the application of the game in learning to speak BIPA which is divided into three parts, namely planning, implementation, and evaluation. The application of the game in learning to speak BIPA is carried out effectively, although it is still in implementation.